Fabrication and application of dimyristoyl phosphatidylcholine biomaterial-based nanocochleates dry powder inhaler for controlled release resveratrol delivery - A. J. Mali; P. A. Joshi; C. Bothiraja; A. P. Pawar (SpringerOpen, 2021)
Abstract Background Resveratrol, a bioactive phytoconstituent, is used to treat chronic respiratory diseases. However, its clinical application was hampered due to its poor bioavailability. In the present study, controlled release of resveratrol loaded nanocochleate-based dry powder inhaler was investigated to improve its biopharmaceutical properties for pulmonary drug delivery. The in vivo toxicity study was performed in the healthy male albino Wistar rats by intracheal administration. Results Resveratrol loaded nanocochleate-based dry powder inhaler was prepared by lyophilizing the resveratrol loaded dimyristoylphosphatidylcholine sodium and calcium ion-based nanocochleates using mannitol as cryoprotectant. Resveratrol loaded nanocochleates showed a particle size and encapsulation efficiency of 329.18 ± 9.43 nm and 76.35 ± 3.65%, respectively. Resveratrol loaded nanocochleate-based dry powder exhibited a particle size of 102.21 ± 9.83 μm and satisfactory flowability with initial burst release followed by extended release up to 96 h. The in vitro drug deposition pattern using multistage cascade impactor showed 1.28-fold improvement in fine particle dose, and the in vivo toxicity potential by histopathological study in albino rats revealed safety of formulation. Conclusions Resveratrol loaded nanocochleate-based dry powder inhaler could serve as an efficient delivery system for the treatment of chronic respiratory diseases. Graphical abstract